Arabidopsis fad4 mutant analysis provides insights into thermo sensing within plant plasma membrane - Chen, Mingjie; Du, Zhenghua; Fang, Dongsheng; Zou, Ming; Thelen, Jay J. (Frontiers in Plant Science, 2026)
Increasing evidence suggests that the plasma membrane is the initial site for temperature sensing. In searching for the contributions of membrane lipids to stress-induced cytosolic calcium, we found that FATTY ACID DESATURASE 4 (FAD4) knockout mutant exhibited an elevated acute cytosolic calcium spike in response to heat shock or oxidative stress, but not cold shock. fad4 mutant plants are more tolerant to heat stress but less tolerant to cold or high light stress. Lipidomic profiling demonstrated that overall phosphatidylglycerol (PG) levels, specifically, PG (36:7) levels, were reduced in the plasma membrane of fad4 mutants. Based on liposome binding assays, calcium channel proteins annexin2 and annexin4 showed higher association with fad4 plasma membranes compared to wild type (WT) control. Fat Western analyses indicated that anionic lipids, including phosphatidylserine (PS), phosphatidic acid (PA), and PG, bind to annexin1, 2, 3, and 4 with variable affinity, with PS binding the most tightly and PG the least. These results support the hypothesis that the plasma membrane is the initial site of thermo sensing in Arabidopsis.